The Problem of Personal Self-Determination in L. I. Bozhovich's Works and its Development from the Viewpoint of the Subject-Centered Approach - Ermolaeva M.V; Lubovsky D.V; Silaeva L.V (Moscow State University of Psychology and Education, 2018)
The article analyzes the understanding of self-determination in L. I. Bozhovich's works, authors present the theoretical context in which self-determination was considered in her researches (development of personality as the mastering of the behavior, self-determination as a free choice). It is shown that three approaches to the study of self-determination in Russian psychology were created on the basis of L.I. Bozhovich's approach to the study of self-determination: self-determination as self-comprehension, as an orientation in the system of social values and as the development of subjectivity. It is shown that L. I. Bozhovich's approach to the study of subjectivity is closest to the subject-centered approach in contemporary Russian psychology. The stages of personality development, outlined in L.I. Bozhovich's works are considered as the stages of subjectivity formation. Authors are planning to create educational practices for adolescents based on their typical activities and aimed to the development of personal reflection as a basis of self-cognition and self-determination.The article analyzes the understanding of self-determination in L. I. Bozhovich's works, authors present the theoretical context in which self-determination was considered in her researches (development of personality as the mastering of the behavior, self-determination as a free choice). It is shown that three approaches to the study of self-determination in Russian psychology were created on the basis of L.I. Bozhovich's approach to the study of self-determination: self-determination as self-comprehension, as an orientation in the system of social values and as the development of subjectivity. It is shown that L. I. Bozhovich's approach to the study of subjectivity is closest to the subject-centered approach in contemporary Russian psychology. The stages of personality development, outlined in L.I. Bozhovich's works are considered as the stages of subjectivity formation. Authors are planning to create educational practices for adolescents based on their typical activities and aimed to the development of personal reflection as a basis of self-cognition and self-determination.